2022
DOI: 10.3390/ijms231911832
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ZnT86D in Neurodevelopment and Pathogenesis of Alzheimer Disease in a Drosophila melanogaster Model

Abstract: Zinc is a fundamental trace element essential for numerous biological processes, and zinc homeostasis is regulated by the Zrt-/Irt-like protein (ZIP) and zinc transporter (ZnT) families. ZnT7 is mainly localized in the Golgi apparatus and endoplasmic reticulum (ER) and transports zinc into these organelles. Although previous studies have reported the role of zinc in animal physiology, little is known about the importance of zinc in the Golgi apparatus and ER in animal development and neurodegenerative diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Lee et al found that ZnT7 is important for neurodevelopment and that the knockdown of ZnT7 did not alter Aβ deposition but worsened neurodegeneration. These results suggest that proper distribution of zinc in the Golgi may be useful in protecting neurons and Alzheimer’s disease [ 54 ] ( Figure 5 ).…”
Section: Effect Of Golgi Stress On Neuropathiesmentioning
confidence: 99%
“…Lee et al found that ZnT7 is important for neurodevelopment and that the knockdown of ZnT7 did not alter Aβ deposition but worsened neurodegeneration. These results suggest that proper distribution of zinc in the Golgi may be useful in protecting neurons and Alzheimer’s disease [ 54 ] ( Figure 5 ).…”
Section: Effect Of Golgi Stress On Neuropathiesmentioning
confidence: 99%
“…Their findings may provide a deeper understanding of the mechanisms through which the consumption of these alimentary products is related to the development of neuronal diseases. In the second paper, by using Drosophila , Lee et al demonstrated that ZnT86D, a Drosophila ortholog of zinc transporter ZnT7, plays an important role in the neurodevelopment and pathogenesis of AD [ 3 ]. RNAi silencing of ZnT86D in neurons induced abnormal neurogenesis and neuronal cell death that resulted in reduced survival rates, locomotor activity, and lifespan.…”
mentioning
confidence: 99%
“…RNAi silencing of ZnT86D in neurons induced abnormal neurogenesis and neuronal cell death that resulted in reduced survival rates, locomotor activity, and lifespan. Interestingly, neuron-specific knockdown of ZnT86D in the AD model fly enhanced apoptosis and neurodegeneration without alterations in the deposition of amyloid beta and susceptibility to oxidative stress [ 3 ]. Since ZnT7 is mainly localized in the Golgi apparatus and endoplasmic reticulum (ER), their findings suggest that proper distribution of zinc in the Golgi apparatus and ER is critical for neuronal development and neuroprotection.…”
mentioning
confidence: 99%